Gender Reconstruction in Indonesian Muslim Families in Hadith Memes - Nikmatullah, Nikmatullah; Rohmaniyah, Inayah; Amrulloh, Zaenudin; Qudsy, Saifuddin Zuhri (Italian Sociological Review, 2024)
Hadith memes are individual expressions of daily socio-religious reality through social media, including negotiating gender in an open and free virtual space. This paper aims to explore gender construction in Muslim families through hadith memes on Facebook pages. Using qualitative methods and a feminist approach, the study shows that the gender reconstruction contained in hadith memes is part of the individuals’ and communities’ freedom of expression in understanding religion through the selection and interpretation of hadith texts according to their knowledge, and dissemination through social media. Gender reconstruction in Muslim families shows debatable opinions between conservative and progressive Muslim groups; Muslim feminists criticize the hegemony of men as a religious authority supporting the patriarchal ideology in social media. This trend is fostered simultaneously with the strengthening of individual religious authority in the digital space to reconstruct and negotiated gender based on the interpretation of the Islamic texts in religious memes.